2022
DOI: 10.1186/s12866-022-02506-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli isolated from urinary tract infection and association between virulence expression and antimicrobial susceptibility

Abstract: Background The capacity of antibiotics to modulate bacterial virulence has raised concerns over the appropriateness of antibiotic therapies, including when dosing strategies fall below sub-therapeutic levels. In this work, we investigated the ability of antibiotics to influence virulence in Escherichia coli isolated from urinary tract infection (UTI). Results Out of 120 isolates, 32.5% carried pap, 21.7% carried hlyA, and 17.5% carried cnf. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Studies performed on UPEC in other countries also reported lower hemolysis rates of 41.5% and 32.3%, in Mexico and Nepal, respectively [ 70 , 91 ]. We also observed that beta-hemolytic isolates were significantly more susceptible to cephalosporins, CIP, and GEN, which may be due to the reduced virulence as a cost of acquiring resistance, as reported previously [ 46 , 73 ]. Hemolytic isolates were also significantly associated with biofilm formation, which agrees with previous reports stating that biofilm-forming UPEC had a higher rate of hemolysin production [ 92 , 93 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Studies performed on UPEC in other countries also reported lower hemolysis rates of 41.5% and 32.3%, in Mexico and Nepal, respectively [ 70 , 91 ]. We also observed that beta-hemolytic isolates were significantly more susceptible to cephalosporins, CIP, and GEN, which may be due to the reduced virulence as a cost of acquiring resistance, as reported previously [ 46 , 73 ]. Hemolytic isolates were also significantly associated with biofilm formation, which agrees with previous reports stating that biofilm-forming UPEC had a higher rate of hemolysin production [ 92 , 93 ].…”
Section: Discussionsupporting
confidence: 87%
“…The isolates' total DNA was extracted using the boiling lysis technique [ 46 ]. Briefly, the overnight culture suspensions of isolates were centrifuged, and the cell pellets were resuspended in 200 µL of nuclease-free water.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effect of sub-MIC level of ciprofloxacin on the virulence gene expression of E. coli was widely studied. For instance, reduced expression of iron acquisition genes, fimbriae genes and hemolysin A gene was observed on exposure to sub-MIC level of ciprofloxacin [3,35]. It was also found that the sub lethal concentration of antibiotics, such as ceftriaxone, can modulate the expression of OMPs in S. Typhi [13].…”
Section: Discussionmentioning
confidence: 96%
“…E. coli is one of the intestinal microbiomes for more than 90% of people 2 , E. coli represents commensal bacteria in the intestine as microflora of animals and humans, some E. coli strains can cause disease in humans, mammals, and birds 3 .E. coli is one of the bacteria that have recently become resistant to different classes of antibiotics through various mechanisms including efflux pump, and decreased cell permeability 4 . They are highly adaptable bacteria that can survive and grow in outdoor environments, involving the river 5 .…”
Section: Introductionmentioning
confidence: 99%